The elderly liver transplant recipients: anxiety, depression, fatigue and life satisfaction - Krenzien, Felix; Krezdorn, Nicco; Morgül, Mehmet H; Wiltberger, Georg; Atanasov, Georgi; Hau, Hans-Michael; Hinz, Andreas; Schmelzle, Moritz; Bartels, Michael; Benzing, Christian (Zeitschrift für Gastroenterologie, 2017)
Introduction Older patients are neglected in clinical trials and are likely to be excluded from liver transplantation (LT). The aim of this study was to assess fatigue, anxiety, depression, and health-related quality of life (HRQoL) in elderly LT recipients.Methods Questionnaires were mailed to patients who underwent LT between 1993 and 2013. Three groups were created: patients ≥ 70, 60 – 69, and < 60 years old. Mental-health status, life satisfaction, and fatigue were assessed using, respectively, the Hospital Anxiety and Depression Scale (HADS), Questions on Life Satisfaction (FLZ-M), and the Multidimensional Fatigue Inventory (MFI-20).Results In total, 276 eligible questionnaires (40.1 %) were received out of 689 patients with a history of LT. No age-related differences were found with regard to anxiety or depression in the study sample. Patients ≥ 70 years old had significantly better life satisfaction in regards to income (p = 0.003) and work (p = 0.005) compared to patients < 60 years. The overall fatigue scores were the highest in patients < 60 years (52.7, SD = 15.8) and ≥ 70 years (52.7, SD = 17.7) compared to patients 60 – 69 years old (48.2, SD = 17.3, p = 0.037).Discussion Advanced age alone should not be considered a contraindication for LT due to potentially poor quality of life outcomes.
Keywords: Lebertransplantation; ältere lebertransplantierte Patienten; Lebensqualität; Fatigue; Angst; Depression